Analysis of the Level of Erosion Hazard By Using Remote Sensing and Geographic Information System in the Sub-Watershed of Rindu Hati - Prayogi Dhuha Brahmanto; Bambang Sulistyo; M. Faiz Barchia (TERRA : Journal of Land Restoration, 2020)
Rindu Hati sub-watershed is located in District of Central Bengkulu, Bengkulu Province, that has flat until montainous topography with various slope and annual rainfall up to 4,032 mm year-1 which possible causes erosion. This research was aimed to analyze soil erosion at Rindu Hati sub-watershed based on the Universal Soil Loss Equation formula, using remote sensing imagery data and by applying GIS technique. USLE method were uses five parameters, those were length and slope factor, rainfall erosivity factor, crop management factor and land conservation , and soil erodibility factor. An overlay analysis has been conducted to obtain the erosion. Then, the result is overlaid with soil depth map to get the level of erosion hazard, which is classified into: very light, light, moderate, heavily, and very heavily. The results showed that the total erosion was 12,410,650.59 tons ha-1 year-1, while its level of erosion hazard were very light (15 tons ha-1 year-1) covering an area of 2,983 ha spreading over community agricultural areas and forest areas, the rate of light erosion (> 15-60 tons ha-1 year-1) has the largest area of covering an area of 10,410.05 ha which scattered in plantation areas having flat topography, moderate erosion rates (> 60-180 tons ha-1 year-1) of 1,317.33 ha spread over land areas with shrub land use and relatively flat topography, heavily erosion rates (> 180- 480 tons ha-1 year-1) covering 1,735.48 ha spread over land with shrub land use but has a hilly topography and very heavily erosion rates (> 480 tons ha-1 year-1) covering 2,700.42 ha located in the mining area. Erosion potential rate mapping will be very helpful in determining good and appropirate land management and conservation in the study area.